Feasibility of the Implementation of Tools for Heart Failure Risk Prediction - Michael C. Wang, MD; Bridget Dolan, PharmD; Xiaoning Huang, PhD; Priya M. Freaney, MD; Benjamin H. Freed, MD; Lourdes Vega, PharmD; Nikola Markoski, PharmD, MBA; Amy Wainright, PharmD; Bonnie Kane, BS, RDCS; Laura E. Seegmiller, MPH; Sanjiv J. Shah, MD; Clyde W. Yancy, MD, MSc; et al. (JACC: Advances)
Background: The 2022 American College of Cardiology/American Heart Association heart failure (HF) guidelines recommended the use of multivariable risk equations to guide HF prevention. However, this strategy has not been prospectively assessed. Objectives: The aim of the study was to determine the feasibility of risk-based prevention of HF. Methods: The FIT-HF (Feasibility of the Implementation of Tools for Heart Failure Risk Prediction) study was a randomized controlled pilot trial. Patients with a predicted 10-year HF risk ≥5% were randomly assigned 1:1 to receive either usual care or collaborative care with a pharmacist. All participants underwent B-type natriuretic peptide (BNP) and high-sensitivity cardiac troponin I (hs-cTn) testing and echocardiography at baseline and 1-year follow-up. The primary outcome, change in BNP at 1 year, was examined using linear mixed models. Secondary outcomes included change in hs-cTn and traditional risk factor levels. Exploratory outcomes included echocardiographic measures and lifestyle measures. Results: Of 101 randomized participants, 82 completed 1-year follow-up and comprised the primary analytic sample. Mean (SD) age was 70.0 (7.0) years, 45% were female, 83% self-identified as White, and mean (SD) predicted 10-year risk of HF was 12.2% (8.0). Baseline mean (SD) BNP (pg/mL) was 40.2 (28.2) and 36.5 (19.6) in the intervention and control arms, respectively. Model-estimated between-arm difference (95% CI) in BNP at 1 year follow-up was −9.0 (−20.6 to 2.6, P = 0.13), and in hs-cTn was −1.8 (−3.5 to −0.2, P = 0.03), favoring the intervention. Differences in other secondary outcomes were not statistically significant. Conclusions: FIT-HF demonstrates the feasibility of enrolling patients based on predicted risk for risk-based HF prevention; larger follow-up studies are needed to determine efficacy and long-term impact of specific preventive interventions. (Feasibility of the Implementation of Tools for Heart Failure Risk Prediction [FIT-HF]; NCT04684264).